Saving Rates of New Zealanders: A Net Wealth Approach - Grant M. Scobie; Katherine Henderson (New Zealand Government, The Treasury, 2009)
Reliable estimates of actual household saving rates in New Zealand have proved elusive as existing sources of data have in the past given disparate estimates, making it difficult to reach a consensus of the real rate of household saving. For the first time in New Zealand, however, longitudinal data on the assets and liabilities of households at the unit record level are becoming available from Statistics New Zealand's multi-year national longitudinal Survey of Family Income and Employment (SoFIE). In this paper we first update estimates from the Reserve Bank's aggregate data on the household sector (a stock approach) and those from Statistics New Zealand's national accounts (a flow approach). These continue to give widely different estimates of the overall household saving rate, although both were negative in 2008 and both below their long-run trend values. We then present initial estimates derived from SoFIE by comparing individuals' net wealth in 2004 with that in 2006 and computing the implied real saving rate on an annual basis. This yielded an overall median estimate of 16%. This is virtually the same as the long-run average annual saving rate measured from the aggregate household balance sheet from RBNZ. Furthermore, the estimated saving rates between 2004 and 2006 for the whole household sector in total are almost identical using RBNZ and SoFIE data. However, it must be stressed that median estimates should be complemented with a measure of dispersion. There is a strikingly wide distribution of saving rates. For example across many categories of individuals around 40% are estimated to have had a decline in net wealth, implying a negative rate of saving. Initial explorations into the reasons for this are undertaken in the paper, but as yet are not fully understood. Measurement errors in the data can account for some of the disparities but much remains for further research. Finally we demonstrate that over the period 2004 to 2006, passive saving in the form of the revaluation of house prices constituted a major part of the total change in net wealth. After removing owner-occupied property as an asset, the median saving rate remained positive at 5%, close to the long run average rate from the aggregate RBNZ data after correcting for changes in house prices.
Keywords: D18; D31; D91; E21; 330; Net wealth; saving; saving rates; unit records; permanent wealth; transitory components; New Zealand; Sparen; Vermögen; Neuseeland